KEDUDUKAN HAK CIPTA DALAM MEWUJUDKAN HAK EKONOMI SEBAGAI UPAYA PERLINDUNGAN TERHADAP INTELLECTUAL PROPERTY RIGHTS - Sari, Indah (JURNAL ILMIAH M-PROGRESS, 2016)
This research aimed at analysing how copyrights could bring about economic rights for innovators and authors. In addition of generating economic rights, copyrights also protecting intellectual property rights. As we know, intellectual property rights is rights obtained from one’s thoughts or ideas, and it has economical values for the innovator and/or author. As it consequence, people required to get license from and grant royalty to the innovator and/or author when they need to gain further these economic values. This condition also valid to the copyrights as contained in law no. 28 of 2014 on Copyrights. Research here focused on economic rights of copyrights; what kind of economic advantages would gained by the innovator and/or author of his/her creation Keywords: Copyrights, Economic Rights, Intellectual Property Rights